Athol Fitzgibbons, The Nature of macroeconomics. InstabiIity and change in the capitalist system, Edward Elgar, Cheitenham & Northampton, 2000, 171 pp. - Crespo, Ricardo F. (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2004)

(untitled)
Fil: Crespo, Ricardo F.. Consejo Nacional de Investigaciones Científicas y Técnicas